Limited value of multiparametric MRI with dynamic contrast-enhanced and diffusion-weighted imaging in non-mass enhancing breast tumors. Issue 156 (November 2022) - Marino, Maria Adele; Avendano, Daly; Sevilimedu, Varadan; Thakur, Sunitha; Martinez, Danny; Lo Gullo, Roberto; Horvat, Joao V.; Helbich, Thomas H.; Baltzer, Pascal A.T.; Pinker, Katja
Highlights: mpMRI shows limited diagnostic value in NME lesions. Across four mpMRI approaches, adapted mpMRI has the highest specificity. Increases in specificity are at the expense of sensitivity and overall diagnostic accuracy. DCE-MRI remains the most sensitive and accurate modality for NME breast cancer detection (94.8–100 %). Abstract: Purpose: To investigate the diagnostic value of multiparametric MRI (mpMRI) including dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and diffusion-weighted imaging (DWI) in non-mass enhancing breast tumors. Method: Patients who underwent mpMRI, who were diagnosed with a suspicious non-mass enhancement (NME) on DCE-MRI (BI-RADS 4/5), and who subsequently underwent image-guided biopsy were retrospectively included. Two radiologists independently evaluated all NMEs, on both DCE-MR images and high- b -value DW images. Different mpMRI reading approaches were evaluated: 1) with a fixed apparent diffusion coefficient (ADC) threshold (<1.3 malignant, ≥1.3 benign) based on the recommendation by the European Society of Breast Imaging (EUSOBI); 2) with a fixed ADC threshold (<1.5 malignant, ≥1.5 benign) based on recently published trial data; 3) with an ADC threshold adapted to the assigned BI-RADS classification using a previously published reading method; and 4) with individually determined best thresholds for each reader. Results: : The final study sample consisted of 66 lesions in 66 patients. DCE-MRI alone had the highest sensitivity for breast cancer detection (94.8–100 %), outperforming all mpMRI reading approaches (R1 74.4–87.1 %, R2 71.7–94.8 %) and DWI alone (R1 74.4 %, R2 79.4 %). The adapted approach achieved the best specificity for both readers (85.1 %), resulting in the best diagnostic accuracy for R1 (86.5 %) but a moderate diagnostic accuracy for R2 (77.2 %). Conclusion: mpMRI has limited added diagnostic value to DCE-MRI in the assessment of NME.